2018
DOI: 10.1029/2018sw001985
|View full text |Cite
|
Sign up to set email alerts
|

Telluric Field Variations as Drivers of Variations in Cathodic Protection Potential on a Natural Gas Pipeline in New Zealand

Abstract: A study of variations in cathodic protection potential on a natural gas pipeline in the North Island of New Zealand is reported. Both the measured pipe‐to‐soil potential (PSP) and the current measured through an installed defect in the pipeline coating show strong correlations with variations in measured magnetic and telluric fields. Contrary to predictions from distributed‐source transmission line theory, analysis shows that the closest correlations of PSP and current are with the component of telluric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Even if the former proves to be the case and annual means are of no assistance in predicting superstorms, characterizing the core of the distribution (as opposed to the extreme tail) is, however, still important in space weather applications where the integral of the space weather activity is of relevance and the threshold to the effect is not in the extreme tail. Examples would include the effect of GICs on pipeline corrosion (Boteler, ; Cole, ; Gummow, ; Ingham & Rodger, ; Pirjola, ; Pirjola et al, ; Pulkkinen et al, ; Viljanen et al, ); the effect of GICs on power grid transformer degradation (Gaunt, ; Kappenman & Radasky, ); the effect of energy deposition in the upper atmosphere on the orbits of LEO satellites and space debris (Doornbos & Klinkrad, ); and the effect of integrated radiation dose on the degradation of spacecraft electronics (Baker, ; Fleetwood et al, ). In all these examples, although the extreme superstorm events have a large effect, they are rare and a much larger number of smaller events, described by the core distribution, can also have a significant integrated effect.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the former proves to be the case and annual means are of no assistance in predicting superstorms, characterizing the core of the distribution (as opposed to the extreme tail) is, however, still important in space weather applications where the integral of the space weather activity is of relevance and the threshold to the effect is not in the extreme tail. Examples would include the effect of GICs on pipeline corrosion (Boteler, ; Cole, ; Gummow, ; Ingham & Rodger, ; Pirjola, ; Pirjola et al, ; Pulkkinen et al, ; Viljanen et al, ); the effect of GICs on power grid transformer degradation (Gaunt, ; Kappenman & Radasky, ); the effect of energy deposition in the upper atmosphere on the orbits of LEO satellites and space debris (Doornbos & Klinkrad, ); and the effect of integrated radiation dose on the degradation of spacecraft electronics (Baker, ; Fleetwood et al, ). In all these examples, although the extreme superstorm events have a large effect, they are rare and a much larger number of smaller events, described by the core distribution, can also have a significant integrated effect.…”
Section: Introductionmentioning
confidence: 99%
“…According to Martin (1993), the high corrosion rate is responsible for the 10 % penetration into the pipe over 14 years. Henriksen et al (1978) studied a Norwegian pipeline with 300 telluric events and found a corrosion rate of 0.04 mm yr −1 caused by these events.…”
Section: Corrosion Rate Estimationmentioning
confidence: 99%
“…Previous works on GICs were done in high latitudes and revealed specific interactions between the disturbances in the solar wind and the geomagnetic field (Campbell, 1980;Fernberg et al, 2007). The effects of GICs in pipelines have also been observed and published in Argentina (Osella et al, 1998), Australia (Marshall et al, 2010), and New Zealand (Ingham and Rodger, 2018) where engineers tried to find ways of dealing with the problem. Boteler and Cookson (1986) showed that the telluric voltage induced on pipelines can be calculated by using distributed source transmission line (DSTL) equations, and the telluric effects in the pipeline are not only influenced by space weather events but also depend on the Earth's conductivity, the pipelines' electromagnetic properties, and the geometric parameters.…”
Section: Introductionmentioning
confidence: 98%
“…The recommended expressions, generically denoted by P, are skill scores of the form given by Shim et al (2011), Murphy (1988), or Liemohn, McCollough, et al (2018. It has been used by Marsal (2015) or Marsal et al (2017) in geomagnetism, and after the work of Torta et al (2014), it has been recurrently used in the GIC literature (Bailey et al, 2018;Blake et al, 2018;Ingham et al, 2017;Ingham & Rodger, 2018;Torta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%